Development of Innovative Business Models for MSMEs in the Indonesian Tourism Sector - Ethan Tan; Sofia Linm; Ryan Teo (Journal of Loomingulisus ja Innovatsioon, 2024)
The Indonesian tourism sector plays a significant role in the national economy, with small and medium-sized enterprises (MSMEs) forming a crucial part of the industry. However, the sector faces several challenges, including market volatility, the impact of the COVID-19 pandemic, and the need for digital transformation. Innovative business models are essential for MSMEs to remain competitive and sustainable in this dynamic environment. This study aims to explore the development of innovative business models for MSMEs in the Indonesian tourism sector, focusing on the factors that drive innovation and the strategies that enable MSMEs to adapt to changing market conditions. The research employs a mixed-methods approach, combining qualitative interviews with MSME owners and quantitative surveys to gather insights into the factors influencing innovation. The findings reveal that digitalization, community-based tourism, and sustainable practices are key drivers of innovation among MSMEs in the sector. However, challenges such as limited access to capital, lack of technical expertise, and inadequate government support hinder the widespread adoption of these innovative models. The study concludes that developing tailored support systems, promoting digital literacy, and encouraging collaboration between MSMEs and local governments are essential to fostering innovation in the tourism sector. These findings contribute to the academic literature on innovation in emerging markets and provide practical recommendations for policymakers and MSMEs.